Impacts and challenges of industry 4.0 in manufacturing: a systematic literature review - Tamires Fernanda Barbosa Nunes; Roselaine Ruviaro Zanini; Ariane Ferreira Porto Rosa; Lizandra Garcia Lupi Vergara (The Journal of Engineering and Exact Sciences)
The concept of Industry 4.0 emerged in Germany as a strategy for innovation and recovery of economic performance and has spread worldwide. The digital transformation proposed by Industry 4.0 is driven by intelligent manufacturing processes, digitalization, flexibility, integration of systems, and real-time analysis of big data generating intelligent processes and services oriented to customer needs. However, despite the opportunities produced by technological innovation, the fourth industrial revolution has established an environment of uncertainty in the labor market and business models reflected throughout the social sphere. Thus, this study aimed to identify the potential impacts and challenges of Industry 4.0 through a systematic literature review (SLR). Our findings pointed to seven potential impacts of Industry 4.0 on manufacturing: (i) environmental, (ii) competitive, (iii) economic, (iv) education, (v) labor market, (vi) business models, and (vii) social. Additionally, six potential challenges faced by manufacturing in adopting digital transformation were found: (i) management, (ii) government, (iii) implementation, (iv) workforce, (v) operation, and (vi) security. The results indicated that accurate understanding of the concepts and scope of Industry 4.0 are under construction and that knowledge sharing will be decisive in shaping the future of the transition from current business models to smart manufacturing.